Online medical advice system (Tele-kesihatan) / Santha Mary Vedamanikkam - Santha Mary, Vedamanikkam (2001)
'TELE-KESIHATAN' (Tele-Kes) is computer information system. The aim or objective of this system is to provide greater access to higher health quality to the users, by harnessing current and emerging multimedia and information technologies. The system provides in formation on diseases , health tips, and treatments. These information will be more customized and personalized. The user can post any comments or any question that is related to this system. This system also has an online doctor, where the user can interact with the doctor through mail. Besides that the system also will provide location of nearest medical center so that in case of emergency the user just can rush to nearest hospital. This system will be updated from time to time according to new health information so that the user are more alert and aware of new diseases. This online medical system will be a web based system so that everyone can get the information wherever they are. And also the use rs will be able to gain more knowledge on health in many perspective.